Praktek Pendekatan Self Regulation Learning pada Peserta Latsar CPNS BPSDM Provinsi Bali Tahun 2021 - Ni Made Suciani (Jurnal Widyaiswara Indonesia, 2022)
The purpose of this study is to describe the practice of the Self Regulation Learning (SRL) approach in forming latsar participants to become independent learners and to describe an increase in learning outcomes and motivation after SLR was practiced in the basic training for civil servant candidates (Latsar CPNS) at BPSDM Bali Province in 2021. This study involved 40 participants class XVI In 2021 at BPSDM Bali Province with 30 participants of teacher and 10 non-teacher at the Bali Provincial Government. The approach used in this study is a mixed method with an embedded experimental design. Data analysis techniques with qualitative analysis and quantitative descriptive analysis. The qualitative analysis will describe the process of implementing the SLR practice. While the quantitative analysis will analyze the increase in learning outcomes and achievement of learning motivation after the practice of SRL. The results showed that the practice was implemented in the four SLR approaches, namely: linking goal-oriented learning; facilitate learning and thinking strategies; diversification of learning opportunities that enable hope of success; and socialize learning in the caring community that is created. These four practices have been described through 15 core practices of evidence-based learning. The second result is that there is an increase in learning outcomes after the implementation of the self-regulation learning approach, namely from the initial score of 70.25, it increases to the final score of 80.69. As for the overall learning motivation, it reached an average of 4,295 with a high category after implementing self-regulation learning in the Latsar CPNS Class XVI latsar at BPSDM Bali Province in 2021. The results of this study are expected to be practiced in learning because it has been proven to have a direct impact on increasing the motivation and learning outcomes of training participants